Alteration of corneal biomechanical properties in patients with dry eye disease. - Vannarut Satitpitakul; Parichart Taweekitikul; Vilavun Puangsricharern; Ngamjit Kasetsuwan; Usanee Reinprayoon; Thanachaporn Kittipibul (PLoS ONE)
Purpose To evaluate the association between symptoms and signs of dry eye diseases (DED) with corneal biomechanical parameters. Methods This cross-sectional study enrolled 81 participants without history of ocular hypertension, glaucoma, keratoconus, corneal edema, contact lens use, diabetes, and ocular surgery. All participants were evaluated for symptoms and signs of DED using OSDI questionnaire, tear film break-up time (TBUT), conjunctival and corneal staining (NEI grading) and Schirmer test. Corneal biomechanical parameters were obtained using Corvis ST. Mixed-effects linear regression analysis was used to determine the association between symptoms and signs of DED with corneal biomechanical parameters. Difference in corneal biomechanical parameter between participants with low (Schirmer value ≤10 mm; LT group) and normal (Schirmer value >10mm; NT group) tear production was analyzed using ANCOVA test. Results The median OSDI scores, TBUT, conjunctival and corneal staining scores as well as Schirmer test were 13±16.5 (range; 0-77), 5.3±4.2 seconds (range; 1.3-11), 0±1 (range; 0-4), 0±2 (ranges; 0-9) and 16±14 mm (range; 0-45) respectively. Regression analysis adjusted with participants' refraction, intraocular pressure, and central corneal thickness showed that OSDI had a negative association with highest concavity radius (P = 0.02). The association between DED signs and corneal biomechanical parameters were found between conjunctival staining scores with second applanation velocity (A2V, P = 0.04), corneal staining scores with second applanation length (A2L, P = 0.01), Schirmer test with first applanation time (A1T, P = 0.04) and first applanation velocity (P = 0.01). In subgroup analysis, there was no difference in corneal biomechanical parameters between participants with low and normal tear production (P>0.05). The associations were found between OSDI with time to highest concavity (P<0.01) and highest displacement of corneal apex (HC-DA, P = 0.04), conjunctival staining scores with A2L (P = 0.01) and A2V (P<0.01) in LT group, and Schirmer test with A1T (P = 0.02) and HC-DA (P = 0.03), corneal staining scores with A2L (P<0.01) in NT group. Conclusions According to in vivo observation with Corvis ST, patients with DED showed more compliant corneas. The increase in dry eye severity was associated with the worsening of corneal biomechanics in both patients with low and normal tear production.